Effect of particle properties on froth stability - Achaye, Innocent (Department of Chemical Engineering, 2017)
The froth flotation process has found substantial usage in the mineral processing industry for over a century and as long as minerals continue to exist in the earth's crust, the demand for upgrading and recovery of these natural yet valuable resources will continue to exist. It relies on the principle that a bubble-particle collision process should be accompanied by the formation of an attachment between the pair. Of particular importance to the flotation process is the stability of froths. This will affect the mass pull, which, in turn, will affect recovery and the grade that is attainable. Froth stability is affected by many factors, viz. machine properties, hydrodynamics within the flotation cell, reagent suites, as well as mineral particle properties. Of particular interest to reagent suites is the frother dosage and its influence on the prevention of coalescence which has been fairly well studied. Regarding froth stability, the frother influences the amount of water that reports to the concentrate as well as the bubble surface viscosity, limiting drainage and subsequent bubble coalescence. Most of the other factors influence the amount of particles that report to the froth, but it is the particle properties that have the overriding influence on the froth stability. It is in the interest of flotation modelling and optimisation to be able to find relationships for the impact of particle properties on froth stability. This project has focussed on the influence of two main particle properties, i.e. size and hydrophobicity, and their interactive effects on froth stability. In order to establish relationships between particle properties and froth stability, two devices were built in the laboratory, i.e. a non-overflowing stability column to measure froth stability and a bench-scale continuous flotation cell to provide metallurgical information, besides being able to measure froth stability using water recovery and froth surface bubble burst rate. In the first part of the investigation, particles of discrete sizes as well as mixtures of particles sizes were utilised at a constant hydrophobicity. Results obtained show a power law relationship between froth stability and particle size, with all particle combinations falling on the same relationship. Froth stability decreased with increasing particle size. A large increase in froth stability occurred for feed particles of average size below 50 μm. This was attributed to particles in the finer range reporting to the froth by both true flotation and entrainment. These fine particles would result in a higher interfilm viscosity resulting in reduced drainage. A useful linear relationship between froth stability and the reciprocal of feed particle size was obtained. The reciprocal of feed particle size was used to represent the specific surface area of the particles. It was found that as the specific surface area of the particles increased, their froth stabilising effect also increased in a linear fashion. In the second part of the investigation, the influence of particle hydrophobicity and the interactive effects of particle size and hydrophobicity on froth stability were explored. In common with other studies, it was found that froth stability increased with increasing particle hydrophobicity up to an optimum value between 66° and 69° and thereafter it decreased. The smallest size particles (28 μm) produced the highest variation in froth stability with increasing hydrophobicity. The response of the coarse particles to froth stability with increasing hydrophobicity was less pronounced. Particle size was found to have a greater influence on froth stability than particle hydrophobicity. Variations in froth stability were about 1.5 times greater for changes in particle size than changes in hydrophobicity over the relatively large ranges of size and hydrophobicity tested. The relationship between froth stability and feed particle specific surface area was investigated at different hydrophobicities and found to be linear for most practical particle sizes. However, a deviation from linearity occurred at very small particles sizes (28 μm) for particles of optimum hydrophobicities. The slopes of the froth stability versus feed specific surface area relationships in the linear region were found to increase with increasing hydrophobicity, up until an optimum contact angle of between 64° and 68°, whereafter they decreased. Thus, this family of curves would allow the prediction of froth stability of varying hydrophobicities on a size-by-size basis. This relationship was shown to hold for two real ores: a platinum-bearing UG2 ore and an Itabirite iron ore. Thus, a simple linear calibration of grind versus froth stability would allow a prediction of froth stability for a particular ore. A Langmuir-type model was developed to relate the froth stability to the concentrate particle surface area. It was found to be a good fit to the experimental data. This shows that it is possible to model froth stability in terms of the particle packing at the air-water interface in much the same way that surfactant molecular packing at the interface is modelled. The increasing particle surface area affects the surface tension of the films and reduces film drainage. In studying the interactive effects of particle size and hydrophobicity, it was found that all data points of all hydrophobicities fell on the same relationship when froth stability was plotted as a function of concentrate surface area. It was therefore, concluded that particle size and hydrophobicity define the amount of particles that will report to the froth phase, but once in the froth, it is the surface area of the particles that will define the froth stability.